THE VALUE OF TARBAWI IN SURAH AL-ASR AS SOLUTIONS FOR OVERCOMING GADGET ADDICTION FOR STUDENTS - Suwarno; Zaini Fasya; Ramsah Ali (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
Gadgets are technological devices designed to simplify human activities. Nearly 60% of Indonesia's population uses gadgets, with students being the largest group. Today's students spend more time playing with gadgets than studying. This study aims to explore the value of tarbawi (Islamic education) in Surah al-Asr as a solution for students in making the most of their time. The study's findings indicate that the value of tarbawi in Surah al-Asr is an education in discipline. Allah swears by time, emphasizing that woe to those who waste time on useless pursuits. Only those who believe and do good deeds, and advise one another on truth and patience, will be saved. Therefore, the solution to becoming a student who does not lose out is first, to use time for learning, to become a generation with intellectual intelligence. Second, to use gadgets for positive purposes, namely by advising one another on truth and patience on social media. Third, to consider how to become useful people in the future by utilizing school opportunities for positive things.